2021
DOI: 10.1101/2021.02.09.430417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relative brain size and cognitive equivalence in fishes

Abstract: There are two well-established facts about vertebrate brains: brains are physiologically costly organs, and both absolute and relative brain size varies greatly between and within the major vertebrate clades. While the costs are relatively clear, scientists struggle to establish how larger brains translate into higher cognitive performance. Part of the challenge is that intuitively larger brains are needed to control larger bodies without any changes in cognitive performance. Therefore, body size needs to be … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
(112 reference statements)
1
5
0
Order By: Relevance
“…Nevertheless, the males did outperform the females in this task despite being larger in body size. Performance in the other tasks, in both males and females, were independent of body size; a finding that fits previous outcomes resulting from a larger dataset on female cleaner fish [41]. It is noteworthy to mention that the observed and tested female cleaners were sexually mature, which means they were at least 1 year old (i.e.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, the males did outperform the females in this task despite being larger in body size. Performance in the other tasks, in both males and females, were independent of body size; a finding that fits previous outcomes resulting from a larger dataset on female cleaner fish [41]. It is noteworthy to mention that the observed and tested female cleaners were sexually mature, which means they were at least 1 year old (i.e.…”
Section: Discussionsupporting
confidence: 84%
“…In other words, larger individuals (within or between sexes) are more likely to be older [ 40 ]. Previous research on cleaner fish has shown that performance levels from various cognitive tasks do not correlate with body size (a proxy for age) [ 41 ]. Therefore, it is unlikely that males will outperform females in any of our four cognitive tasks just because they are larger and older.…”
Section: Introductionmentioning
confidence: 99%
“…The latter vary between 0.4 and 0.5 within species [Tsuboi et al, 2018]. For fishes, Triki et al [2021] obtained a mean intraspecific slope of 0.49 that is independent of body size variation. Furthermore, studied one fish species, i.e., the cleaner fish Labroides dimidiatus in more detail.…”
Section: Validation Of the Slope Estimatementioning
confidence: 95%
“…Therefore, our sample in this respect adequately represents the reality of the size distributions in the sampled populations. The lack of positive correlation between the brain size and FL shown here in hatchery individuals is unusual for wild fishes, where body size is a strong predictor of brain volume (e.g., Triki et al, 2021 ). Previous studies on the evolution of encephalization in mammals have suggested that relative brain size depends on selection pressure on the size of the brain as well as on the overall body size (Smaers et al, 2012 ).…”
Section: Discussionmentioning
confidence: 59%